(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article describes the newest methods of motivating staff, not focusing solely on material incentives. The role of incentives in the process of work motivation as specific external irritants is considered. In the article, incentives are also considered as levers of influence, which concentrate certain motives of a person. The theory of expectations of V. Vrum, which states that the employee is obliged to have such needs, which can be significantly satisfied with the result of anticipated rewards, is characterized. The rules that are intended to help increase the motivation of the company’s employees are outlined. The growth dynamics of the number of IT specialists in Ukraine and their geographical identity are analyzed. It is revealed that geographically Ukraine is divided into five IT hubs (Kyiv, Odesa, Lviv, Dnipro, Kharkiv), which accumulate 75% of all IT employees in Ukraine. Accordingly, startup projects and the latest developments of the IT-sphere are implemented and based in these hubs. The IT sector employees in Ternopil were interviewed to identify the main factors that influence their motivation. The main age category of employees in IT companies is young people aged 18 to 25 years (68.3%), and 25 to 45 years (31.7%). The number of men working in the IT sector is 63.3% and women - 36.7%, which means that the prevalence of men in the companies surveyed is significant. In our opinion, this situation is explained by the change of priorities in the young generation and the desire of women to develop new professions in the IT field. The largest number of respondents work in companies up to a year, and the least number of employees work at the same company for more than five years, which indicates that the companies have insufficient staff turnover policies. The study confirmed that motivation focused solely on monetary incentives is not sufficient. According to the survey, it was found that professional growth and comfortable psychological climate play no less important role in the motivation of IT professionals than material incentives. Besides, the curiosity of the accomplished tasks, the workplace, stability, free schedule, the ability to work outside the office, the status, and the brand of the company is dramatically important.